Does sustainable corporate governance have an impact on materiality disclosure quality in integrated reporting? International evidence - Patrick Velte (Sustainable Development, 2022)
This study examines the influence of sustainable corporate governance on the materiality disclosure quality (MDQ) in integrated reporting in an international setting. Referring to stakeholder theory, we focus on gender diversity, sustainability committees, and sustainability-related executive compensation. Based on European and South African firms (672 firm-year observations) between 2014 and 2019, we found that board gender diversity and sustainability-related executive compensation were significantly positively linked to MDQ. However, the implementation of sustainability committees does not affect the MDQ. Thus, only specific sustainable corporate governance variables in concrete contexts may be related to integrated reporting decisions. We also included Chief Executive Officer (CEO) power (pay slice, ownership, and tenure) as a moderator variable due to the strategic impact of CEOs, based on upper echelons theory, and found that the link between our included sustainable corporate governance variables and MDQ was weakened. Our results are robust to several variations and provide valuable insights for research, business practice and future regulations on integrated reporting. In view of massive regulatory reform initiatives on sustainable corporate governance and integrated reporting, sustainability expertise (also with regard to CEOs) should be better addressed in boards of directors during the next years to come.
Keywords: 330; gender diversity; integrated reporting; sustainability expertise; sustainable corporate governance; sustainable management compensation